V-SINEs: A New Superfamily of Vertebrate SINEs That Are Widespread in Vertebrate Genomes and Retain a Strongly Conserved Segment within Each Repetitive Unit - Ogiwara, Ikuo; Miya, Masaki; Ohshima, Kazuhiko; Okada, Norihiro (Genome Research, 2002)
We have identified a new superfamily of vertebrate short interspersed repetitive elements (SINEs), designated V-SINEs, that are widespread in fishes and frogs. Each V-SINE includes a central conserved domain preceded by a 5′-end tRNA-related region and followed by a potentially recombinogenic (TG)n tract, with a 3′ tail derived from the 3′ untranslated region (UTR) of the corresponding partner long interspersed repetitive element (LINE) that encodes a functional reverse transcriptase. The central domain is strongly conserved and is even found in SINEs in the lamprey genome, suggesting that V-SINEs might be ∼550 Myr old or older in view of the timing of divergence of the lamprey lineage from the bony fish lineage. The central conserved domain might have been subject to some form of positive selection. Although the contemporary 3′ tails of V-SINEs differ from one another, it is possible that the original 3′ tail might have been replaced, via recombination, by the 3′ tails of more active partner LINEs, thereby retaining retropositional activity and the ability to survive for long periods on the evolutionary time scale. It seems plausible that V-SINEs may have some function(s) that have been maintained by the coevolution of SINEs and LINEs during the evolution of vertebrates.[The sequences reported in this paper have been deposited in the DDBJ/GenBank database under accession nos.AB072981–AB073004. Supplemental figures are available online athttp://www.genome.org.]